The ETV6-MECOM fusion protein promotes EMT-related properties by repressing the transactivation activity of E-cadherin promoter in K562 leukemia cells - Qian Li; Furong Wang; Xuehong Zhang; Shuqing Liu; Ming-Zhong Sun; Jinsong Yan (Biochemistry and Biophysics Reports, 2024)
The ETV6-MECOM fusion gene, produced by the rare and recurrent chromosomal translocation t(3; 12) (q26; p13), is associated with high mortality and short survival in myeloid leukemia. However, its function and underlying mechanisms in leukemia progression remain unknown. In this study, leukemia-stable K562 cells expressing the ETV6-MECOM fusion protein were used to investigate the effects of the ETV6-MECOM oncoprotein. K562-ETV6-MECOM cells were undifferentiated and had reduced colony formation, increased cell migration and invasion, and increased sphere number and diameter in a spheroid formation assay, presenting epithelial-to-mesenchymal transition (EMT) traits. The expression of E-cadherin, a hallmark of EMT, was significantly downregulated at the transcriptional and translational level in K562-ETV6-MECOM cells to explore the mechanistic basis of EMT. Stepwise truncation, DNA sequence deletion, mutation analysis for E-cadherin promoter transactivation, and a dual luciferase assay indicated that the regulatory region of ETV6-MECOM is located in the DNA motif −1116 TTAAAA−1111 of E-cadherin promoter. Moreover, a chromatin immunoprecipitation assay showed that this oncoprotein binds to the DNA motif −1116 TTAAAA−1111 with the anti-EVI1 antibody. Although ETV6-MECOM upregulated the expressions of EMT master regulators, including SNAIL, SLUG, ZEB2, and TWIST2, their knockdown had no effect on EMT-related properties. However, overexpression of E-cadherin eliminated EMT traits in the presence of the ETV6-MECOM oncoprotein. These data confirmed that the ETV6-MECOM oncoprotein, not SNAIL, SLUG, ZEB2, or TWIST2, plays a critical role in inducing EMT traits in leukemia K562 cells. ETV6-MECOM induces EMT-related properties by downregulating the transcriptional expression of E-cadherin and repressing its transactivation activity by binding to its core motif −1116TTAAAA−1111 in leukemia K562 cells. These findings could contribute to the development of a therapeutic target for patients with myeloid leukemia characterized by ETV6-MECOM.